Nitrogen in cereal systems: Opportunities for sustainable agricultural growth - Anupam Das; Chakraborty, Debashis (SATSA, 2024)
Nitrogen is the most important nutrient in plant production. Nitrogen management is also essential to ensure global food security while reducing environmental degradation and stabilize disequilibrium. To maintain N balance in an agricultural ecosystem, the value of N inputs must equal N. Soil organic matter (SOM) is an important indicator of soil fertility, a source of energy for heterotrophic organisms, and an important source of plant nutrients. particularly nitrogen in the form of soil organic matter (SON). Progress has been made in developing effective nitrogen management techniques as well as good agricultural practices to increase yields and efficient nitrogen use while reducing nitrogen loads. There are many technologies that farmers can use, such as sowing at higher plant densities, soil test-based fertilizer N application, split N fertilizer applications, fertigation, site-specific N management, new fertilizer formulations such as controlled release nitrification inhibitors and nano-fertilizer formulations in order to encourage the adoption by farmers. Finally, for sustainable agricultural growth, campaign against the misuse of nitrogen fertilizer and policies to improve soil quality need to be promoted.